1966
DOI: 10.1177/001440296603300104
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Speech Behavior and Language Comprehension of Fourteen Children Diagnosed Atypical or Autistic

Abstract: A case study approach used informal and controlled clinical observations and analyses of tape recordings during a two year period to develop detailed descriptions of the speech behavior, language comprehension, and general functioning of fourteen institutionalized children diagnosed autistic or atypical. In speech behavior, the children could be classified as a talking group, from whom identifiable words were heard, or a vocalization group, from whom phonations were heard without any resemblance to words. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 2 publications
0
55
0
2
Order By: Relevance
“…Germane to the study of speech processing in ASD, strong empirical evidence has accumulated from behavioral studies showing that individuals with ASD have pronounced deficits for extracting prosodic information from speech, which conveys emotional state information regarding the speaker through intonation and rhythm (46). Importantly, it has been shown that, in TD individuals, the processing of prosodic information is performed in right-hemisphere temporal cortex (34) and right-hemisphere amygdala (47).…”
Section: Brain Circuitry Underlying Prosody and Emotional Informationmentioning
confidence: 99%
“…Germane to the study of speech processing in ASD, strong empirical evidence has accumulated from behavioral studies showing that individuals with ASD have pronounced deficits for extracting prosodic information from speech, which conveys emotional state information regarding the speaker through intonation and rhythm (46). Importantly, it has been shown that, in TD individuals, the processing of prosodic information is performed in right-hemisphere temporal cortex (34) and right-hemisphere amygdala (47).…”
Section: Brain Circuitry Underlying Prosody and Emotional Informationmentioning
confidence: 99%
“…However, since the first delineation of the autistic syndrome (Kanner, 1943), abnormal suprasegmentals have been frequently identified as a core feature of the syndrome for individuals with autism who speak (Baltaxe & Simmons, 1985Fay & Schuler, 1980;Ornitz & Ritvo, 1976;Paul, 1987;Pronovost, Wakstein, & Wakstein, 1966;Rutter & Lockyer, 1967;Tager-Flusberg, 1981). Differences noted in early, observational reports included monotonic or machine-like intonation, deficits in the use of pitch and control of volume, deficiencies in vocal quality, and use of aberrant stress patterns.…”
Section: Speech and Prosody Characteristics Of Individuals With Pervamentioning
confidence: 99%
“…Note that such deficits would predict stress errors crossing both grammatical and pragmatic contexts, whereas the present study found errors only in the latter domain. Pronovost et al (1966) reported wide variations in pitch and loudness among speakers with autism. In the present study, individuals with HFA and AS differed from typical speakers in loudness (too loud) and pitch (too high), but the magnitudes of effects were small.…”
Section: Stressmentioning
confidence: 99%
“…Following up on Kanner's (1946) observations, early clinical studies were focused on describing the abnormal language used by children with autism, which included atypical intonation and vocal quality, idiosyncratic use of words and stereotyped phrases, echolalia, and pronoun reversal (e.g., Cunningham, 1966;Goldfarb, Braunstein, & Lorge, 1956;Pronovost, Wakstein, & Wakstein, 1966;Shapiro & Fish, 1969). The majority of these published reports were neither methodologically systematic nor developmentally informed as they relied mostly on poorly defined clinical samples or single case histories.…”
Section: Classic Studies Of Language In Autismmentioning
confidence: 99%